Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.celrep.2017.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic and Transcriptomic Basis of Lysosomal Dysfunction in Progranulin Deficiency

Abstract: Summary Defective lysosomal function defines many neurodegenerative diseases, such as neuronal ceroid lipofuscinoses (NCL) and Niemann-Pick type C (NPC), and is implicated in Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD-TDP) with progranulin (PGRN) deficiency. Here, we show that PGRN is involved in lysosomal homeostasis and lipid metabolism. PGRN deficiency alters lysosome abundance and morphology in mouse neurons. Using an unbiased lipidomic approach, we found that brain lipid composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 53 publications
11
86
0
Order By: Relevance
“…Overexpression of human progranulin can rescue toxicity from overexpression of TDP‐43 mutants in zebrafish and heterozygous loss of progranulin enhances toxicity from TDP‐43 overexpression in worms , indicating that haploinsufficiency of progranulin may render neurons susceptible to TDP‐43 toxicity. As in humans, Grn knockout mice display gene‐dosage dependent lysosomal pathology, with upregulation of lysosomal proteins and an increase in the number of lysosomes in both heterozygous and homozygous mice . Perhaps unsurprisingly homozygous knockout mice also present accumulation of lipofuscin, as found in the homozygous disorder NCL .…”
Section: Genetic Models Of Ftdmentioning
confidence: 96%
“…Overexpression of human progranulin can rescue toxicity from overexpression of TDP‐43 mutants in zebrafish and heterozygous loss of progranulin enhances toxicity from TDP‐43 overexpression in worms , indicating that haploinsufficiency of progranulin may render neurons susceptible to TDP‐43 toxicity. As in humans, Grn knockout mice display gene‐dosage dependent lysosomal pathology, with upregulation of lysosomal proteins and an increase in the number of lysosomes in both heterozygous and homozygous mice . Perhaps unsurprisingly homozygous knockout mice also present accumulation of lipofuscin, as found in the homozygous disorder NCL .…”
Section: Genetic Models Of Ftdmentioning
confidence: 96%
“…lipid droplet accumulation, compared to wild type macrophages 78 . In addition, a recent study reported that loss of GRN leads to intracellular and intra-lysosomal accumulation of long polyunsaturated triacylglyerides 79 in the brains of humans and mice. Since triacylglycerides (TAG) are a major component of lipid droplets in LAM, it is possible that lipid droplet accumulation in GRN deficient microglia contributes to elevated TAG levels in brains lacking GRN.…”
Section: Lam In Neurodegenerationmentioning
confidence: 99%
“…Likewise, astrocytes are known to bind and degrade extracellular amyloid-β, a key player in Alzheimer's disease (Wyss-Coray et al, 2003;Koistinaho et al, 2004). Recent work established a strong link of both Parkinson's disease and FTD with lysosomal storage disorders (LSDs) (Deng et al, 2015;Burbulla et al, 2017;Evers et al, 2017). LSDs are a large group of rare inherited metabolic disorders with defective lysosome function resulting in faulty degradation and recycling of cellular constituents.…”
Section: Discussionmentioning
confidence: 99%